Ketahanan Keluarga di Era Stigma Digital Perspektif Al-Qur’an - Amin, Rajabbul; Islamiyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This study aims to analyze how the construction of digital social stigma influences perceptions of family happiness and how Qur’anic values can strengthen family resilience amid the visual culture of social media. Using a qualitative approach through literature studies, content analysis of phenomena on TikTok and Instagram, and thematic (maudhu’i) interpretation of relevant Qur’anic verses, this research finds that digital pressure significantly affects perceptions of happiness and may lead to relational conflict and identity crises within families. The values of sakinah, mawaddah, and rahmah (Qur’an, Ar-Rum: 21), along with the principles in Al-Hujurat: 12 and Al-Isra: 36, serve as spiritual and social foundations for building resilient Muslim families. The findings highlight the importance of integrating Qur’anic values with digital literacy to foster strong and enduring families in the era of visual culture.